Super visible : the story of the women of Marvel Comics - Stohl, Margaret (G13, 2025)
"Inspired by the hit podcast Women of Marvel and cowritten by the #1 New York Times bestselling coauthor of Beautiful Creatures, this stunning book celebrates the women who have helped make Marvel one of the most successful comics and entertainment companies in the world."--